Risk factors for work-related injury among farm workers: A one-year study - Molineri, Ana Inés (2015)
A 1-year prospective study was carried out to look for risk factors of farm-related injuries in Egusquiza, Santa Fe (Argentina). Information on demographic characteristics and occupational accidents was collected on (N=110, n=78) farm workers by means of personal interviews using a structured questionnaire. Monthly telephone contact was then maintained with the workers for 1 year to document all farm-related injuries. Data analysis included incidence rate, χ 2 and logistic regression. Sixty-nine farm-related injuries were reported during the study period, six injuries being the maximum number affecting one worker. A total of 46.3% of the workers suffered at least one injury during the year. The incidence rate was 7.5 injuries/100 individual-month at risk. Medical assistance was needed in 26.8% of the cases and 5.8% of the injuries caused at least 1 day off work. Hospitalization for at least 1 day was required for 2.9% of the injured workers. Previous work-related injury in the family (p=0.005) (odds ratio (OR)=4.6, 95% confidence interval (CI)=1.6–13.3) and worker’s activity (p=0.021) (OR=3.7, 95%CI=1.2–11.6) were associated with the dependent variable work injury. Agricultural and livestock farming are of great importance for the national economy. Workers’ training on farm safety may play a key role to prevent work-related injuries and diseases.